Effects of alfalfa saponin extract on mRNA expression of Ldlr, LXRα, and FXR in BRL cells - Liang, Xin-ping (Zhejiang University Press, 2015)

(untitled) (J Zhejiang Univ Sci B)
We studied the effects of alfalfa saponin extract (ASE) on low density lipoprotein receptor (Ldlr), liver X receptor α (LXRα), and farnesoid X receptor (FXR) in normal and hyperlipidemic Buffalo rat liver (BRL) cells. Normal and hyperlipidemic BRL cells were divided into eight groups: normal, or normal cells treated with 50, 100, and 150 mg/L ASE, hyperlipidemic, or hyperlipidemic cells treated with 50, 100, and 150 mg/L ASE. After treatment for 24 h, Ldlr, LXRα, and FXR mRNA expression levels were measured by quantitative real-time polymerase chain reaction (qRT-PCR). Data showed that mRNA expression of Ldlr in normal BRL cells was significantly up-regulated by ASE treatment and mRNA expressions of LXRα and FXR were significantly down-regulated both in normal and hyperlipidemic BRL cells after ASE treatment. Thus, ASE might ameliorate hepatic steatosis by regulating genes involved in cholesterol metabolism, including up-regulation of Ldlr as well as down-regulation of LXRα and FXR.